Assembly of hydrothermally stable ethane-bridged periodic mesoporous organosilicas with spherical and wormlike structures - Shylesh, S.; Jha, Ratnesh Kumar; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Hydrothermally stable periodic mesoporous organosilicas with spherical as well as wormlike frame structures were synthesised by two different synthesis routes using the silsesquioxane precursor, 1,2-bis (triethoxy silyl) ethane (BTEE) and surfactant octadecyl trimethyl ammonium (ODTA), under basic conditions. The materials were characterized by PXRD, SEM, TEM, N-2 adsorption-desorption, FT-IR, Si-29 MAS NMR, C-13 CP MAS NMR and TG-DTA techniques. Characterization techniques revealed that the morphology of the hybrid material prepared from pure silsesquioxane precursor resulted in spherical particles while a combination of tetra ethyl orthosilicate and 1,2-bis (triethoxy silyl) ethane (90:10 ratio) resulted in materials having wormlike structures. Hydrothermal stability of the hybrid material was evaluated by refluxing the sample under boiling water for various time periods and was compared with that of a periodic mesoporous silica material, Si-MCM-41. Results showed that the hybrid material is stable up to 100 h in boiling water, with the existence of d(100) peak, while the mesopore structure of Si-MCM-41 get destroyed even after a 12 h reflux time. The improved hydrothermal stability of the hybrid material is related to the more hydrophobic environment induced inside the pore channels, due to the presence of integrating ethane groups in the wall channels. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: hybrid mesoporous materials; Hydrothermal stability; spherical particles; wormlike structures